The Bangsamoro Framework Agreement and the Mindanao problem foregrounding historical and cultural facts and concepts for social justice and peace in the Southern Philippines. - Sakili, Abraham P. (Asian Studies, 2012)
WITH THE SIGNING of the Bangsamoro Framework Agreement between the Philippine Government (GPH) and the Moro Islamic Liberation Front (MILF) on October 15, 2012, the hope for peace among the Muslims in Mindanao has become alive.